A study on fault self-recovery of interconnected co-phase traction network for heavy haul railway - PENG Ye; WANG Shuai; WANG Kewen (机车电传动)
In order to adapt to the continuous growth of freight traffic volume, the heavy haul railways have undergone the transportation capacity upgrading and transformation. The co-phase and bilateral power supply technologies can be adopted to cancel the phase breaks along the line and effectively improve the traction power supply capacity. A power supply transformation scheme suitable for the interconnected co-phase power supply traction network of heavy haul railway was put forward in this paper, and such a scheme can meet the needs of grid-based power supply of the traction network and continuous operation of the locomotive. Moreover, due to the fact that the existing protection and tripping/reclosing scheme could not satisfy the safety requirements for the interconnected co-phase power supply system, based on the operation characteristics of the interconnected co-phase traction network and the locomotive, the sectionalized protection and fault self-recovery strategies for traction network were proposed to realize the fault-oriented safety of traction network and ensure the minimum outage interval of traction network with fault. Finally, the simulation results verified the accuracy and effectiveness of the scheme. This scheme can provide important support for the interconnected co-phase power supply transformation for heavy haul railway, and plays a positive role in ensuring the safe transportation of goods.